Revising eternity : 27 Latter-day Saint men reflect on modern relationships - Welker, Holly; Mason, Patrick Q. (University of Illinois Press, 2022)
"Marriage's central role in The Church of Jesus Christ of Latter-day Saints distinguishes the faith while simultaneously reflecting widespread American beliefs. But what does Latter-day Saint marriage mean for men? Holly Welker presents a collection of essays exploring this question. The essayists provide insight into challenges involving sexuality, physical and emotional illness, addiction, loss of faith, infidelity, sexual orientation, and other topics. Conversational and heartfelt, the writings reveal the varied experiences of Latter-day Saint marriage against the backdrop of a society transformed by everything from economic issues affecting marriage to evolving ideas about gender. An insightful exploration of the gap between human realities and engrained ideals, Revising Eternity sheds light on how Latter-day Saint men view and experience marriage today"--